2008
DOI: 10.1158/0008-5472.can-08-0121
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule E2F Inhibitor Blocks Growth in a Melanoma Culture Model

Abstract: HLM006474 was identified using a computer-based virtual screen and the known crystal structure of the DNA bound E2F4/DP2 heterodimer. Treatment of multiple cell lines with HLM006474 resulted in the loss of intracellular E2F4 DNA-binding activity as measured by electrophoretic mobility shift assay within hours. Overnight exposure to HLM006474 resulted in down regulation of total E2F4 protein as well as known E2F targets. The effects of HLM006474 treatment on different cell lines varied, but included a reduction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 28 publications
3
71
0
Order By: Relevance
“…Treatment of hESCs with the E2F inhibitor HLM006474 (ref. 28) significantly decreased hESC proliferation (Fig. 2d) and led to an increase in cell death (Fig.…”
Section: Rb Activation In Hescs Induces Cell Cycle Arrest and Deathmentioning
confidence: 87%
“…Treatment of hESCs with the E2F inhibitor HLM006474 (ref. 28) significantly decreased hESC proliferation (Fig. 2d) and led to an increase in cell death (Fig.…”
Section: Rb Activation In Hescs Induces Cell Cycle Arrest and Deathmentioning
confidence: 87%
“…Several studies have shown the usefulness of this approach for inhibition of tumor cell growth. 49,50 Our results indicate that depleting E2F activity in a context in which the pRb and the p53 pathways are functional, which is the situation of most non-cancerous cells in an organism, renders cells susceptible to become Figure 8 Disruption of p53 in E2F1/E2F2 mutant mice promotes development of thymic lymphomas and compromises survival. (a) Life spans of WT, E2F1/E2F2 DKO, p53 − / − and E2F1/E2F2/p53 TKO mice (n = 15/genotype) analyzed using a log-rank non-parametric test and expressed as Kaplan-Meier survival curves (E2F1/E2F2 DKO versus WT, Po0.0001; E2F1/E2F2/p53 TKO versus WT, Po0.0001; E2F1/E2F2/p53 TKO versus E2F1/E2F2 DKO, Po0.0001; E2F1/E2F2/p53 TKO versus p53 − / − , Po0.0001).…”
Section: E2f-p53 Regulatory Axis In Tissue Homeostasismentioning
confidence: 93%
“…A key goal in the immediate future will be to identify the consequences of RB1 inactivation that can be best exploited therapeutically to target RB1 mutant tumors. little progress has been reported on this subject, and only a few compounds have been available for research (Ma et al 2008;Sangwan et al 2012;Kurtyka et al 2014).…”
Section: The Translation Of Rb Researchmentioning
confidence: 99%